Numerical Simulation for Engine/Airframe Interaction Effects of the BWB300 on Aerodynamic Performances - Gang Yu; Dong Li; Yue Shu; Zeyu Zhang (International Journal of Aerospace Engineering)
The engine/airframe interaction effects of the BWB300 on aerodynamic performances were analyzed by using the numerical simulation method. The BWB300 is a 300-seat Blended Wing Body airplane designed by the Airplane Concept Design Institute of Northwestern Polytechnical University. The engine model used for simulation was simplified as a powered nacelle. The results indicated the following: at high speed, although the engine/airframe interaction effects on the aerodynamic forces were not significant, the airframe’s upper surface flow was greatly changed; at low speed, the airframe’s aerodynamic forces (of the airplane with/without the engine) were greatly different, especially at high attack angles, i.e., the effect of the engine suction caused the engine configuration aerodynamic forces of the airframe to be bigger than those without the engine; and the engine’s installation resulting in the different development of flow separation at the airframe’s upper surface caused greater obvious differences between the 2 configurations at high angles and low speed. Moreover, at low-speed high attack angles, the separated flow from the blended area caused serious distortion at the fan inlet of the engine.